A Narrative Review of Cerebellar Malfunctions and Sleep Disturbances - Song, Bijia; Zhu, Jun-Chao (Frontiers in Neuroscience, 2021)
Cerebellar malfunctions significantly impact the regulation of the sleep-wakefulness transition. The possible mechanism for this effect is still unknown. Evidence on the role of cerebellar processing in the sleep-wake cycle is derived mainly from animal studies, and clinical management of the sleep-wake cycle is also challenging. The purpose of this review is to investigate the role of cerebellar activity during normal sleep and the association between cerebellar dysfunction and sleep disorders. Large-scale, multicenter trials are still needed to confirm these findings and provide early identification and intervention strategies to improve cerebellar function and the sleep quality of patients.